STRATEGI KOMUNIKASI BRANDING PRODUK UNGGULAN DAERAH DALAM PENGUATAN EKONOMI UMKM KABUPATEN BERAU - IRA INDRIANI (ECO-BUILD, 2026)
Background: Berau Regency possesses diverse flagship products, such as processed fishery products, handicrafts, traditional batik, local coffee, and forest honey, most of which have met market quality standards and business legality requirements. However, this potential has not been matched by an effective branding communication strategy, causing local products to struggle in competing with similar products from other regions. Objective: This study aims to examine the branding communication strategy of regional flagship products in strengthening the SME economy in Berau Regency, employing a descriptive qualitative approach through in-depth interviews, non-participant observation, and documentation involving SME actors, the Department of Cooperatives, Industry, and Trade, and consumers as triangulation informants, with data analyzed using the interactive model of Miles, Huberman, and Saldaña. Results: The findings reveal that the branding communication strategies implemented by SME actors remain partial, marked by weak brand storytelling, inconsistent visual identity, reliance on conventional promotional channels, and limited government assistance in branding development. Conclusion: The gap between good product quality and weak branding communication strategy is the main factor behind the low competitiveness of local products, indicating the need to integrate communication strategies grounded in local narratives, strengthen visual identity, optimize digital media, and foster synergy between local government and SME actors to promote sustainable regional economic development.